The human body - not only a biological entity - Grzegorz Wysiadecki; Stanisław Orkisz; Krzysztof Balawender; Michał Golberg; Andrzej Żytkowski (Elsevier, 2024)
Background: The human body is a complex entity composed of organs and systems that pull together to fulfill specific functions necessary to sustain life. This seemingly simple definition, however, needs to be revised since the importance of the human body goes far beyond its biological role. Aim: In anatomical literature, much attention is paid to the human body's material (morphological) aspects. Contrary to such an approach, the presented considerations aim to devote attention solely to the body itself, which for centuries has been an object of interest for scientists and a source of inspiration for artists. Conclusions: With the progress of science and technology, the boundaries and taboos related to the human body are almost constantly changing. Modern anatomy and neuroanatomy can develop in greater depth and breadth, and the human body can be understood in a much more comprehensive range of contexts. Science is increasingly exploring the structure and functioning of the body and, thanks to the development of modern psychology, its association with the mind.